2016
DOI: 10.2139/ssrn.2760802
|View full text |Cite
|
Sign up to set email alerts
|

Do the Rich (Really) Consume Higher-Quality Goods? Evidence from International Trade Data

Abstract: Using average import prices (unit values) as proxies for quality, a large body of the international trade literature finds both theoretical and empirical support for the positive relationship between importer income and quality of imports. Several authors, however, argue that the empirical evidence of the link between income and product quality might be spurious, since import prices could be affected by other factors than product quality. This paper takes into account this issue with a new theoretical and empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Gale and Huang (2007), Yu andAbler (2009), andAbler (2010) empirically showed that the income elasticity of the demand for food quality is significantly positive. Merellay and Santabárbara (2017) found evidence of a positive link between importer income and quality of imports. If high-quality foods have a lower wastage rate owing to their superior flavor, freshness or ease of preparation, then one might expect the municipal FWR to depend on the composition of food consumption across high-and low-quality products.…”
Section: B Conceptual Frameworkmentioning
confidence: 96%
“…Gale and Huang (2007), Yu andAbler (2009), andAbler (2010) empirically showed that the income elasticity of the demand for food quality is significantly positive. Merellay and Santabárbara (2017) found evidence of a positive link between importer income and quality of imports. If high-quality foods have a lower wastage rate owing to their superior flavor, freshness or ease of preparation, then one might expect the municipal FWR to depend on the composition of food consumption across high-and low-quality products.…”
Section: B Conceptual Frameworkmentioning
confidence: 96%